Analisis Perilaku Pedagang Ikan Di Desa Sidokumpul Kecamatan Paciran Lamongan Ditinjau Dalam Perspektif Ekonomi Islam - Maásah, Zahrotul (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Paciran Subdistrict is an area located in the northern region of Lamongan Regency. Among the 17 villages included in Paciran Subdistrict, one of them is Sidokumpul Village, where the residents work as fishermen, making fish the main commodity of the community. The fish they catch from the sea are directly sold to earn money, which is used as a means of exchange to meet their daily needs. However, as Muslims, they have an obligation to implement the teachings of Islam, such as how Islam provides guidelines on proper production methods, how to market goods correctly and truthfully, and how to consume goods in a good and proper manner. Therefore, both traders and consumers are required to apply values according to the religion they adhere to, which is Islam.Islam itself teaches humanity not to deceive one another in transactions, as a form of applying the principle of justice for all, so that social disparities can be reduced and human welfare can be achieved. The threat from Allah, as stated in the holy book Al-Qur'an, against traders (producers) who commit fraud is indeed severe. Although they may not immediately receive sanctions in this world, in the hereafter they will face eternal punishment. It is there that all deeds committed during their lifetime will be accounted for. May we not be among such people.